Study on folk remedies using medicinal plants by Karbi tribe of West Karbi Anglong District, Assam, India (Indian Journal of Traditional Knowledge (IJTK), 2023)
The present study was conducted to document the indigenous knowledge on folk medicines of the Karbi tribe in three remote villages of West Karbi Anglong district, Assam. A total of 80 ethnomedicinal plants recorded were used in treatment of 31 different ailments. Data were collected through restructured questionnaire and quantitative analysis was done. Herbaceous plants occupied the maximum numbers and leaves were the most used plant part among the other parts. The Fic value ranged from 0.74-1, and the used value (UV) ranged from 0.02-1.2; Azadirachta indica was found to be have the highest UV. The study has revealed the pattern of people-plant interactions in the region and the importance of plant medicines playing a vital role in the health care practices and survival of the forest dwellers. There is utmost need of documenting the ethnomedicinal practices of Karbi tribe as they are passing those knowledge generations after generations only by means of practical utilizations without proper pharmacopoeia.